Structural equation modeling identifies markers of damage and function in the aging male Fischer 344 rat. (June 2016) - Grunz-Borgmann, Elizabeth A.; Nichols, LaNita A.; Wiedmeyer, Charles E.; Spagnoli, Sean; Trzeciakowski, Jerome P.; Parrish, Alan R.
Highlights: Changes in renal structure and function begin as early as 16 months in the male Fischer 344 rat. Proteinuria and urinary Kim-1 are predictors of age-related changes in renal structure and function. Structural equation modeling can discriminate factors associated with either Damage or Function. Abstract: The male Fischer 344 rat is an established model to study progressive renal dysfunction that is similar, but not identical, to chronic kidney disease (CKD) in humans. These studies were designed to assess age-dependent alterations in renal structure and function at late-life timepoints, 16–24 months. Elevations in BUN and plasma creatinine were not significant until 24 months, however, elevations in the more sensitive markers of function, plasma cystatin C and proteinuria, were detectable at 16 and 18 months, respectively. Interestingly, cystatin C levels were not corrected by caloric restriction. Urinary Kim-1, a marker of CKD, was elevated as early as 16 months. Klotho gene expression was significantly decreased at 24 months, but not at earlier timepoints. Alterations in renal structure, glomerulosclerosis and tubulointerstitial fibrosis, were noted at 16 months, with little change from 18 to 24 months. Tubulointerstitial inflammation was increased at 16 months, and remained similar from 18 to 24 months. A SEM (structural equation modeling) model of age-related renal dysfunction suggests that proteinuria is a marker of renal damage, while urinary Kim-1 is a marker of both damage and function. Taken together, these results demonstrate that age-dependent nephropathy begins as early as 16 months and progresses rapidly over the next 8 months.